The Effect of Counseling, Training, and Intrinsic Motivation on Employee Productivity through Resilience in Startup Companies - Marlita, Devi; Liana, Esti; Suhendra, Agus; Perwitasari, Erni Pratiwi; Handayani, Sinai; Sismiati, Sismiati (Kuras Institute, 2025)
The novelty of this study lies in its holistic approach. It integrates counseling, training, and intrinsic motivation as key factors influencing employee resilience, which ultimately impacts productivity in startup environments. Unlike previous studies that typically examine one or two factors in isolation, this research offers a comprehensive perspective by demonstrating how the combination of these three elements strengthens employee resilience in facing the dynamic challenges of startup settings, thereby leading to increased productivity. The aim of this study is to examine the factors influencing productivity using a descriptive quantitative approach. Primary data were collected through a questionnaire utilizing a Likert scale ranging from 1 to 5 (strongly disagree to strongly agree), completed by employees at startup companies. The study involved 160 respondents and was analyzed using Smart Partial Least Squares. The results indicate that counseling, training, and intrinsic motivation do not have a positive or significant effect on resilience. However, resilience has a positive and significant effect on employee productivity. Additionally, intrinsic motivation does not have a positive or significant indirect effect on employee productivity through resilience.